Weight, height and BMI references in Elazig: an east Anatolian city - Pirincci, Edibe; Mazicioglu, M. Mumtaz; Berberoglu, Ufuk; Acik, Yasemin; Durmus, Birsen; Ozturk, Ahmet (Turkish J Pediatrics, 2011)
The aim of this study was to produce the growth references for Elazig children aged 6-11 years. Data were collected in eight primary schools of Elazig in 2007. Age-and gender-specific height, weight and body mass index (BMI) references were produced with LMS (Lambda-Mu-Sigma) method and compared with reported values in an Anatolian and a metropolitan city. A total of 3,342 (1,634 females, 1,708 males) children aged 6-11 years from among 4,258 students were included in the study. Age-and gender-specific height, weight and BMI references were produced. The 3rd-97th percentiles were detected to be higher than the range of percentiles between 6-11-year-old children. We consider that this first local reference for Elazig will provide a useful tool for health planning and monitoring of growth and development.
Keywords: body mass index; growth; height; percentiles; weight